The Cambridge Kant lexicon - Wuerth, Julian (Cambridge University Press, 2021)
"Already within his own lifetime, Immanuel Kant achieved renown as one of the leading philosophers of all time. Just as quickly, however, his philosophy gained notoriety as one of the most difficult to understand. Even Kant's contemporary and friend, the great German rationalist philosopher Moses Mendelssohn, complained in a letter to Kant about the "nerve-juice-consuming" (Nervensaftverzehrende) nature of Kant's philosophy (C, 10:308 [April 10, 1783]/CEC:190). One problem is the highly technical terminology in Kant's philosophy. Another is the highly systematic nature of Kant's philosophy, combined with its sheer size: individual parts of Kant's philosophy, including its words, doctrines, and works, are interconnected in a vast systematic whole spanning his recorded thought from across four decades, so that the meaning of these individual parts often remains obscure when considered in isolation. With such interpretive obstacles in the path of Kant's readers, it was not long before Kant lexicons appeared, in both German and English"--
Literaturverzeichnis: Seite 791-797
Keywords: Kant, Immanuel -- 1724-1804 -- Encyclopedias; Wörterbuch; Kant, Immanuel